2017
DOI: 10.1074/jbc.m117.801936
|View full text |Cite
|
Sign up to set email alerts
|

An N-terminal di-proline motif is essential for fatty acid–dependent degradation of Δ9-desaturase in Drosophila

Abstract: Edited by Dennis R. VoelkerThe ⌬9-fatty acid desaturase introduces a double bond at the ⌬9 position of the acyl moiety of acyl-CoA and regulates the cellular levels of unsaturated fatty acids. However, it is unclear how ⌬9-desaturase expression is regulated in response to changes in the levels of fatty acid desaturation. In this study, we found that the degradation of DESAT1, the sole ⌬9-desaturase in the Drosophila cell line S2, was significantly enhanced when the amounts of unsaturated acyl chains of membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 38 publications
2
34
0
Order By: Relevance
“…While the degradation rate of SCD1 protein is irrespective of the cellular levels of unsaturated fatty acids, 33) we recently reported that the expression level of Δ9-desaturase is posttranslationally regulated by the cellular fatty acid composition in Drosophila melanogaster. 34) Drosophila melanogaster is a model organism that provides advantages for the study of mechanisms underlying the expression and function of Δ9desaturase. 34) First, DESAT1 is the sole fatty acid desaturase that introduces a cis double bond into acyl chain of acyl-CoA in typical Drosophila cell lines such as S2 cells because another fatty acid desaturase, DESAT2, is not expressed.…”
Section: Regulation Of the δ9-desaturase Expression Levelmentioning
confidence: 99%
“…While the degradation rate of SCD1 protein is irrespective of the cellular levels of unsaturated fatty acids, 33) we recently reported that the expression level of Δ9-desaturase is posttranslationally regulated by the cellular fatty acid composition in Drosophila melanogaster. 34) Drosophila melanogaster is a model organism that provides advantages for the study of mechanisms underlying the expression and function of Δ9desaturase. 34) First, DESAT1 is the sole fatty acid desaturase that introduces a cis double bond into acyl chain of acyl-CoA in typical Drosophila cell lines such as S2 cells because another fatty acid desaturase, DESAT2, is not expressed.…”
Section: Regulation Of the δ9-desaturase Expression Levelmentioning
confidence: 99%
“…However, none of the known regulatory mechanisms are directly responsive to changes in the levels of fatty acid desaturation among cellular lipids, raising the question as to how cells coordinate desaturase activity in response to changing environmental conditions. A new study by Murakami et al (2) provides one answer with the discovery of a fatty acid saturation-sensitive pathway for protein degradation in Drosophila that surprisingly depends on a di-proline motif in the N-terminal region of the desaturase.…”
mentioning
confidence: 99%
“…In the study by Murakami et al (2), the authors focus on the Drosophila enzyme DESAT1, the only desaturase expressed in the S2 cell line. Using a polyclonal antibody raised against a C-terminal peptide from the enzyme, they measured DESAT1 levels upon treatment of cells with saturated, monounsaturated, or polyunsaturated fatty acids.…”
mentioning
confidence: 99%
See 2 more Smart Citations